Electrocardiographic findings in patients with arrhythmogenic cardiomyopathy and right bundle branch block ventricular tachycardia - Laredo, Mikael; Tovia-Brodie, Oholi; Milman, Anat; Michowitz, Yoav; Roudijk, Rob W; Peretto, Giovanni; Badenco, Nicolas; Te Riele, Anneline S J M; Sala, Simone; Duthoit, Guillaume; Arbelo, Elena; Ninni, Sandro; et al. (Europace, 2023)
AIMS: Little is known about patients with right bundle branch block (RBBB)-ventricular tachycardia (VT) and arrhythmogenic cardiomyopathy (ACM). Our aims were: (i) to describe electrocardiogram (ECG) characteristics of sinus rhythm (SR) and VT; (ii) to correlate SR with RBBB-VT ECGs; and (iii) to compare VT ECGs with electro-anatomic mapping (EAM) data. METHODS AND RESULTS: From the European Survey on ACM, 70 patients with spontaneous RBBB-VT were included. Putative left ventricular (LV) sites of origin (SOOs) were estimated with a VT-axis-derived methodology and confirmed by EAM data when available. Overall, 49 (70%) patients met definite Task Force Criteria. Low QRS voltage predominated in lateral leads (n = 37, 55%), but QRS fragmentation was more frequent in inferior leads (n = 15, 23%). T-wave inversion (TWI) was equally frequent in inferior (n = 28, 42%) and lateral (n = 27, 40%) leads. TWI in inferior leads was associated with reduced LV ejection fraction (LVEF; 46 ± 10 vs. 53 ± 8, P = 0.02). Regarding SOOs, the inferior wall harboured 31 (46%) SOOs, followed by the lateral wall (n = 17, 25%), the anterior wall (n = 15, 22%), and the septum (n = 4, 6%). EAM data were available for 16 patients and showed good concordance with the putative SOOs. In all patients with superior-axis RBBB-VT who underwent endo-epicardial VT activation mapping, VT originated from the LV. CONCLUSIONS: In patients with ACM and RBBB-VT, RBBB-VTs originated mainly from the inferior and lateral LV walls. SR depolarization and repolarization abnormalities were frequent and associated with underlying variants.
Keywords: Cardiomyopathies; elektrokardiografie; Bundle-Branch Block; blokáda Tawarova raménka; Electrocardiography; lidé; kardiomyopatie; Heart Ventricles; Tachycardia, Ventricular; komorová tachykardie; srdeční komory; Humans